REPORT ON THE PHYTOPLANKTON PIGMENTS MEASURED DURING THE JARE-25 CRUISE TO SYOWA STATION, ANTARCTICA, NOVEMBER 1983 TO APRIL 1984 - ハマダ, エツユキ; タニグチ, アキラ; オカザキ, ミホコ; ナイトウ, ヤスヒコ; HAMADA, Etuyuki; TANIGUCHI, Akira; OKAZAKI, Mihoko; NAITO, Yasuhiko (National Institute of Polar Research, 1985)
P(論文) departmental bulletin paper